Fast‐flowing LBE corrosion of the SiC pump impeller: Numerical and experimental investigations. Issue 1 (6th September 2022) - Li, Xianhui; Zeng, Xian; Zhao, Zhanchong; Zhang, Xiaoxin; Yan, Qingzhi; Zhang, Youyuan; Wen, Yuying; Yang, Xuanbing; Mao, Feng
Abstract: In order to determine the stress state and the specific dynamic corrosion behaviors of the cooling pump impeller in the liquid lead‐bismuth eutectic alloy (LBE), the numerical and the experimental investigations on the fast‐flowing LBE corrosion behaviors of the SiC impeller were conducted. The distributions of stress and displacement of the SiC impeller were simulated, and then the microstructure and mechanical properties of the corroded impeller were characterized. The results indicated that the SiC impeller met the strength requirement of 1000 rpm in LBE, and the dynamic LBE corrosion had little effect upon structure safety of the SiC impeller. The maximum stresses of the SiC impeller without and with LBE loading were .452 and 9.736 MPa, respectively. The maximum displacements of the SiC impeller without and with LBE loading were 76.385 and 4.096 μm, respectively. The LBE loading reduced the axial displacement of the impeller and acted as an impeller stabilizer to some extent. Blade elongating and flapping were the main vibration mode of the SiC impeller. The mechanical properties of the SiC impellers before and after corrosion were basically the same.